1975
DOI: 10.1084/jem.142.6.1509
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for the induction of immunological tolerance by antigen feeding: antigen-antibody complexes.

Abstract: We have previously reported on the induction, in mice, of a systemic (splenic) immune response with IgA as the dominant antibody, as a result of a short (4 day) intragastric immunization course with foreign erythrocytes. This response was followed by a prolonged period of hyporesponsiveness to similarly administered antigen. Here it is shown that this hyporesponsiveness is also manifested towards antigen given intraperitoneally, and that one is therefore dealing with tolerance, not with failure to absorb antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1
1

Year Published

1976
1976
1998
1998

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(45 citation statements)
references
References 15 publications
0
43
1
1
Order By: Relevance
“…The reason for the absence of a pronounced serum response after oral immunization is not clear; however, the induction of a selective systemic hyporesponsiveness could be considered (43).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the absence of a pronounced serum response after oral immunization is not clear; however, the induction of a selective systemic hyporesponsiveness could be considered (43).…”
Section: Discussionmentioning
confidence: 99%
“…The scientific acceptance of oral immunization is limited because results often seem to be contradic tory. Several studies reported the induction of ge nuine forms of systemic tolerance after oral feeding of antigens like ovalbumin, P-lactoglobulin or erythro cytes [13][14][15]. Systemic tolerance and mucosal immun ity may appear concomitantly after oral immuniza tion, and antigen feeding is associated with the devel opment of regulatory antigen-specific suppressor and helper T cells [16,17], The type of antigen may also play an important role because a difference in muco sal immunogenicity between bacterial and food anti gens has been reported [ 15].…”
Section: Discussionmentioning
confidence: 99%
“…However, circulating antibody -predomi nantly IgM isotype -and antigen-antibody complexes suppressed the immune response to particulate antigens such as bacteria or erythrocytes in erythrocyte-fed mice [36,[38][39][40],…”
Section: Oral Tolerancementioning
confidence: 99%